Characteristics of Body Measurement and Shape of Garut Sheep and Its Crosses with Other Breeds - Inounu, Ismeth; ., Erfan; Mulyono, R.H. (Indonesian Journal of Animal and Veterinary Sciences, 2009)
It is important to know body measurement because it could be used to estimate body weight as well as to differentiate the chrateristic of body measurement and shape of animal due to different breed or environment. This research was carried out to study morphometric characteristic of body size and body shape from 78 of Garut sheep (GG), 29 HG sheep {crossbred between St. Croix (HH) and Garut sheep (GG)}, 36 MG sheep {crossbred between Mouton Charollais (MM) and Garut sheep (GG)}, 62 MHG sheep (MG x HG) and 38 HMG sheep (HG x MG). Body part measured were wither height (X1), rump height (x2), body length (X3), chest width (X4), chest depth (X5), hip width (X6), chest girth (X7), cannon circumference (X8) and hip length (X9). Data obeserved were analised using t test and Principle Components Analysis (PCA). Based on PCA it was showen that chest girth was the primary identity for body measurement on males and females of Garut, HG, MG, MHG and HMG with its Eigenvector value 0.689; 0.709; 0.689 and 0.681 respectively. The primary indentity for body shape of Garut sheep were chest girth and hip heigth with Eigenvector value -0.600 and 0.551 respectively. The primary indentity for body shape of HG sheep were body length with Eigenvector value -0.725. The primary indentity for body shape of MG sheep were chest girth, rump heigth, and wither heigth with Eigenvectors value: -0.600; 0.558 and 0.555 respectively. The primary indentity for body shape of MHG sheep was wither height with Eigenvector value 0.608. The primary indentity for body shape of HMG was body length with Eigenvector value 0.764. Body shape of HG and MG sheep is different than that of Garut sheep, but the body shape of MHG and HMG were close to Garut body shape. This result indicated that the adaptability to environment of HMG and MHG is close to that of Garut sheep. Key words: Sheep, Body Size, Body Shape.